"That was one of my most difficult and biggest challenges": experiences, preconditions and preventive measures of health-oriented leadership in virtual teams - A qualitative study with virtual leaders - Ilona Efimov; Volker Harth; Stefanie Mache (BMC, 2024)
Abstract Background Health-oriented leadership (HoL) has a positive impact on health- and work-related outcomes of employees in face-to-face settings. Increased digitization during the COVID-19 pandemic has led to many changes and increased job demands. According to current state of research, HoL in virtual teamwork is insufficiently researched. The aim of the study is to examine the experiences of virtual leaders during the COVID-19 pandemic and to identify preconditions and preventive measures for promoting HoL. Method Using a qualitative study design, semi-structured, guide-based telephone interviews were conducted with 16 German virtual leaders between May and July 2021. The collected data were inductively analyzed and interpreted using qualitative content analysis according to Mayring. Explorative analyses of differences between leaders with and without pre-pandemic experiences with virtual leadership were made. Results Results indicated that leaders, regardless of pre-pandemic experiences with virtual leadership, faced diverse challenges in implementing HoL in virtual teamwork during the COVID-19 pandemic. Virtual leaders perceived personal preconditions (e.g., leaders' characteristics or behaviors), organizational preconditions (support by management or open-minded corporate culture), social preconditions (e.g., social support by team) and technical preconditions (e.g., sufficient technical equipment) as conducive to implementation of HoL. Almost all leaders with pre-pandemic experience identified a need for structural preventive measures, whereas almost all leaders without pre-pandemic experience reported a need for behavioral preventive measures in order to promote HoL in virtual teams. Conclusions This study suggests that implementing HoL in virtual teamwork is challenging, complex and requires adjustments in leadership behavior. Thereby, the study provides initial empirical findings for a holistic approach to HoL implementation in virtual teams, considering beneficial multilevel preconditions. Due to a limited generalization of present results, longitudinal and interventional studies will be necessary for the analysis of causal relationships in future research. In particular, a holistic research perspective in order to understand the complex, contextual interdependencies of leadership is recommended. In practice, based on a differentiated needs analysis, structural preventive measures for a holistic organizational development as well as behavioral preventive measures for ongoing personnel development are recommended.